Gestão ambiental como estratégia de análise para sustentabilidade em cidades históricas sergipanas - Nascimento, Luciana Gomes Machado (2023)
The disharmony produced by the relationship between society and nature, which happens more complexly in historical cities, taking into consideration that its urban growth happened in the context of its time, in living conditions different from the current ones, provokes a series of questions about environmental management in these places, including regarding the historical and specific characteristics of these cities in the elaboration of urban and environmental planning. It is important that in the planning process, the multiple realities and potentialities of each site are included and discussed, in accordance with the principles of sustainable development. In this context, this research has as general objective to analyze the environmental management of historical cities of São Cristóvão/SE and Laranjeiras/SE, with the intention of identifying which actions legitimize the sustainable characteristics in these cities. The methodology applied to the research was based on the quasi-quantitative approach, since to achieve the proposed objectives, this study used both approaches, using the structuralist method, with practical and exploratory character, since it takes the knowledge produced for the application in practice, in view of the scarcity of material produced in relation to the researched theme. The research techniques used were the application of questionnaires to determine sustainability indicators and satisfaction indexes, landscape study and interviews. Throughout this research, the concepts of environmental management and sustainable cities were approached and the relations between historical cities and the environment were analyzed, drawing a parallel between historic cities as a model of sustainable cities, based on various perspectives, which makes this an interdisciplinary research, dealing with a current and necessary theme, scarce of publications and easy replicability, these elements being necessary for the development of a Doctoral thesis. The research is directly related to SDG 11 – Sustainable Cities and Communities and sought to align the dimensions addressed through from sustainability indicators to the other Sustainable Development Goals. As a result, the indicators found obtained an average of 0.42 in the city of Laranjeiras and 0.55 in the city of São Cristóvão. Through the Lighthouse of Sustainability it was noticed that none of the indicators was considered sustainable, on the contrary, unsustainable indicators were found among the results, noting that the selected historic cities are not considered sustainable. The results found were analyzed through the Landscape Study, revealing the fragilities of the selected cities and clarifying some reasons for the results of the indicators found through the research. It is concluded that it is necessary to strengthen the existing relationship between the local population and visitors to historic cities with the environmental, architectural and cultural heritage, through initiatives, mainly of the municipal public power, which should foster the environmental management of these cities, which is the main challenge to achieve sustainability.